Composite Train Brake Blocks Used in KKBW 50 ton wagon Failure Analysis - ADYTIA GIRSANG (NIM 13103144), CHRISTIAN
Brake block is an important part of the train braking system. Failure of brake block will decrease the reliability of overall train operation. Recently, life time period of composite brake blocks that are used in KKBW 50 ton wagon became shorter due to this failure. In this final project, author limited failure analysis under static loading and mechanical properties of the brake block. There are several step for this research, they are: site observation, analyzing of composite brake block material, stresses and failure. Material of this composite brake block analyzed by hardness testing, bending testing, compression testing, friction testing, density calculation, dimension measurement and fraktography. Then, the stresses of composite brake block due to several case of braking load are analyzed by using ANSYS 11.0 software. There are several mode of this composite brake block failure, they are: fracture and break of composite brake block, material of this composite brake block separated from backing plate and the backing plate was in plastic deformed condition. If radius of holder is larger than radius of backing plate, clearance will result and then, if this brake block used for larger radius of wheel, bending load will apply. Combination of this two condition, will increase bending load applied over braking mechanism. Because the total number of cross breaking strength of composite brake block is not enough to withstand the bending load for this condition, failure occured. In order to prevent the same failure occured in the future, bending load must be reduced.